Rethinking Consanguineous Marriages in a Diasporic Setting: A Case Study of ar-Rashidiyya Kinship Community in Germany - Jaraba, Mahmoud (Journal of Family History, 2024)
This article explores the changing landscape of consanguineous marriages among Germany's ar-Rashidiyya community, originally from Turkey's Mardin province. The study employs ethnographic methods to understand how younger members are questioning entrenched marital norms, influenced by factors like migration, education, familial conflicts, individualism, and health concerns. Challenging misconceptions linking these practices to ‘clan crime,’ the article delves into the nuanced relationship between cultural tradition and individual agency. It concludes that consanguineous marriages within the community are no longer rigid practices, but are becoming increasingly adaptable due to both internal community dynamics and wider societal influences.
CRIS-Team Scopus Importer:2024-05-17
Keywords: ar-Rashidiyya community; consanguineous marriages; cultural adaptation; generational transitions; Germany; health concerns; Kinship; ‘Clan crime’